Analisis Kualitatif Peran Nilai-Nilai Ekonomi Islam dalam Mendukung Ketahanan Ekonomi Masyarakat di Negara-Negara Muslim pada Era Digital - Siti Ayu Juliyah; Mukhtar Ulum; Saefullah Fattah (Maslahah : Jurnal Manajemen dan Ekonomi Syariah, 2026)
The development of digital technology has driven significant economic transformation in various countries, including Muslim countries. Economic digitalization offers various opportunities, such as increased transaction efficiency, expanded market access, and strengthened financial inclusion. However, this development also presents various challenges, such as low Islamic financial literacy, the risk of technology misuse, and the emergence of economic practices inconsistent with Islamic principles. This study aims to analyze the role of Islamic economic values ​​in supporting the economic resilience of communities in Muslim countries in the digital era. The study used a descriptive qualitative approach with library research methods. Data were obtained from various literature sources, such as scientific journals, books, academic articles, and reports relevant to Islamic economics, economic resilience, and the digital economy for the 2021–2026 period. Data analysis was conducted using content analysis techniques through the stages of data reduction, data presentation, and drawing conclusions. The results show that Islamic economic values, such as justice, honesty, trustworthiness, and the prohibition of riba (usury), gharar (gharar), and maysir (gambling), play a crucial role in creating more transparent, ethical, and sustainable digital economic activities. Furthermore, the development of Sharia-compliant fintech, Sharia-compliant digital financial services, and Sharia-compliant business platforms also supports increased financial inclusion and community economic resilience. Therefore, integrating digital technology and Islamic economic values ​​can be a strategy for strengthening the economic resilience of communities in Muslim countries.